Motivational Coaching Cues Can Modulate Prefrontal Cortex Activity and Perceptual Responses of Elite Football Players During High‐Intensity Interval Training: A Randomised Crossover fNIRS Study. - Han, Sanghyuk; Ahn, SoYoung; Sung, Yunho; Seo, Ji‐won; Li, Xinxing; Han, Seungoh; Kim, Chaewoon; Song, Wook (European Journal of Sport Science, 2026)
Football coaches commonly provide verbal encouragement and exercise end‐point feedback to sustain players' effort by enhancing motivation during fitness training such as high‐intensity interval training (HIIT). However, the influence of such cues on the prefrontal cortex (PFC), a region involved in exercise cessation decisions, remains unclear. Therefore, this study aimed to compare the effect of motivational cues on PFC activation during HIIT using functional near‐infrared spectroscopy, alongside physiological and perceptual responses. Twenty‐two male elite footballers completed two randomised crossover HIIT sessions on a cycle ergometer, with and without motivational cues. Each session consisted of 12 repetitions of 30‐s high‐intensity bouts, each interspersed with a 30‐s active recovery bout. Heart rate, lactate concentration, rating of perceived exertion (RPE), motivation‐related questionnaires and oxygenated haemoglobin (HbO2) concentration in the PFC were measured throughout HIIT. Although physiological responses were similar between conditions, perceived difficulty, assessed every three HIIT bouts, was significantly lower under the motivational condition, with lower RPE (p = 0.038) and higher motivation (p = 0.049), engagement (p = 0.038) and mood (p = 0.009) scores, particularly after the 9th repetition. From the 10th to 12th repetition of HIIT, the HbO2 concentrations of the orbitofrontal cortex and frontopolar PFC were significantly lower under the motivational condition (p = 0.040 and p = 0.036, respectively), whereas the dorsolateral and ventrolateral PFC showed no significant difference between conditions. In conclusion, motivational cues reduce central PFC activity during the most fatiguing phases of HIIT, reflecting enhanced neural efficiency under motivation despite equivalent physical workloads. Highlights: Motivational coaching cues lead to lower perceptual difficulties and reduced central PFC demand during the later phase of HIIT when fatigue is most pronounced, indicating greater neural efficiency despite equivalent workloads.Differences in the central and lateral PFC responses may reflect region‐specific functional roles in the neural processing of motivational stimuli during repeated and fatiguing exercise.Coaches can employ motivational cues as a match strategy to delay performance impairment from prolonged physical and cognitive loads by attenuating central PFC activation and perceived effort.